Perspektif Budaya Ketimuran dalam Film Disney Princess - Saputri, Nur Amala (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2022)
This study aims to see the depiction of the meaning of eastern culture in the Disney Princess film 2020-2021. Disney as a global film company that is very thick with stories of western culture is now slowly starting to reconstruct eastern culture as a manifestation of its tolerance and openness to cultural diversity in the world. The method used is a semiotic analysis of Roland Barthes' model which sees a message meaning based on symbols ideologically. Researchers chose 2 Disney Princess films, namely Mulan (2020) and the film Raya and The Last Dragon (2021) as objects of research. Data collection was done by film observation and literature study. Researchers do documentation by screenshotting scenes and scenes that show symbols of eastern culture in both films. Then the screenshot images will be sorted based on the type of scene classification. The results of this study there are 4 forms of meaning of eastern culture, namely ideology or belief, attitude towards nature, collectivism, and lifestyle. The four cultural forms are practiced every day as a form of eastern cultural image represented in these two Disney films. Ironically, Disney still preserves the orientalization and Otherness of Eastern culture as a colonialism of Western hegemony.